Implementasi Security Pada Load Balancing Layanan Web Multidomain Dengan SSL - Muhammad Rouvan Amiruddin; Sabriansyah Rizqika Akbar; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Load balancing is a mechanism of sharing on the traffic load to multiple servers in a balance way. An accumulation of excessive traffic load on the server will make system performance decreases. Therefore, the way to implement an optimal and secure system with a large number of incoming traffic so it is necessary to apply a load balancing mechanism. By implementing the load balancing mechanism using HAProxy will make the traffic on network runs optimally because the traffic load will be distributed on two or more connection lines in a balance way. Through the implementation of the system, the server performance becomes more optimal in the absence of overload on a server. In order to generate a secure exchange of data between the client and server, it needs to implement the SSL protocol. By implementing the SSL protocol on this system, the exchange of data between the client and server will be secure Because it is already encrypted. In this system, the number of clients is a very influential part on the performance of server response. The more number of clients will make the server response to the client will get longer while the throughput get a the results decreased and if the system receives a request of more than 500 clients then get the request error of 10.4%.